The Effect of Using the Ispring Suite 11 Application on Indonesian Language Learning Outcomes for Eighth-Grade Students at MTs Negeri 1 Sidenreng Rappang - Karisma; Abdul Kahar; Hasanuddin (MultiTech Publisher, 2024)
This study aims to determine the effect of using the Ispring Suite 11 application on the Indonesian language learning outcomes of eighth-grade students at MTs Negeri 1 Sidenreng Rappang for the 2023/2024 academic year. The population of this study comprised all eighth-grade students, totaling 205 students, with a sample of 60 students, including 30 experimental class students (VIII-A) and 30 control class students (VIII C). Data were collected using observation and post-test techniques. The results of the Minimum Completeness Criteria (KKM) analysis showed that the average score of the experimental class was 74.5, higher than the control class, which averaged 67.1. In the experimental class, 15 students achieved the complete category, while in the control class, only 9 students did. Therefore, the null hypothesis (H0), stating that the Ispring Suite 11 application does not affect the Indonesian language learning outcomes of eighth-grade students, was rejected, and the alternative hypothesis (Ha) was accepted. In conclusion, the use of the Ispring Suite 11 application positively influences the Indonesian language learning outcomes of eighth-grade students at MTs Negeri 1 Sidenreng Rappang.